Examination of pre-school teachers' opinions on mixed age groups in education - Okan Sarigoz; Duygu Deveci (Intelektual Pustaka Media Utama, 2023)
This research was conducted in order to determine the opinions of preschool teachers on eduation with a mixed age group in preschool education. In the research, the case study method, one of the qualitative research methods, was used in order to examine the opinions of the teachers in detail. The study group of the research consists of 12 pre-school teachers who were selected by the criterion sampling method, one of the purposive sampling methods, working in the schools affiliated to the Ministry of National Education in the Kirikhan District of Hatay Province and teaching in classes of mixed age groups. The data of the research were obtained with a semi-structured interview form applied to pre-school teachers. As a result of the research, it was concluded that teaching in a mixed-age classroom gave teachers different perspectives on experiences and events, and that teachers had the most difficulty in preparing a joint education plan suitable for all age levels. Furthermore, in the research, it was concluded that receiving education with a mixed-age group supports the development of the students, gives responsibility to the older students, reinforces their knowledge, and gives exemplary behaviors to the younger students.